Hip Fracture in Asia with a Special Focus in the Oldest Old: A Brief Review - Ching-Lung Cheung; Shun-Cheong Ho; Suhas Krishnamoorthy; Xiaowen Zhang (Journal of Clinical Rheumatology and Immunology, 2022)
Osteoporosis is a prevalent disease globally, with fragility fracture being the clinical outcome. Hip fracture is mostly associated with morbidity, immobility, and mortality among all fragility fractures. Although earlier studies in the 1990s projected that half of the hip fractures in the world will occur in Asia by 2050, epidemiology studies in Asia are inadequate. On the other hand, although the stabilizing or reducing trend of hip fracture incidence was reported in some countries or regions, the total number of hip fractures may still increase due to the rapid increase of the oldest old population. The oldest old usually have the highest fracture incidence, while the available treatment and management of osteoporosis for them are suboptimal. The undertreatment could be due to the “unfavorable” risk–benefit profile, lack of fracture prediction tool for the oldest old, and the presence of multiple comorbidities. A strategic management plan for osteoporosis in the oldest old can help cope with the coming “fracture tsunami” and achieve the “healthy aging” goal among the oldest old. Here, we reviewed the recent Asian epidemiology studies on hip fracture, focusing on the current treatment, fracture prediction, and comorbidities of the oldest old.